2021
DOI: 10.1097/mrr.0000000000000491
|View full text |Cite
|
Sign up to set email alerts
|

Young individuals with stroke in rehabilitation: a cohort study

Abstract: Stroke in younger populations is a public health crisis and the prevalence is rising. Little is known about the progress of younger individuals with stroke in rehabilitation. Characterization of the course and speed of recovery is needed so that rehabilitation professionals can set goals and make decisions. This was a cohort study with data extracted from electronic medical records. Participants were 408 individuals diagnosed with stroke who participated in inpatient rehabilitation in an urban, academic medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In general, younger patients exhibit better functional recovery and outcomes than older groups [105], with higher rates of younger patients achieving mRS scores of 0-1 or 0-2 at follow-up [11,106]. This may partly be due to an increase likelihood of receiving rehabilitative care [105]. Additionally, despite early benefits, a prospective study demonstrated that 20-year mortality rates among premature stroke patients are significantly higher than the general populace when matched for age, sex, and calendar-year [104].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In general, younger patients exhibit better functional recovery and outcomes than older groups [105], with higher rates of younger patients achieving mRS scores of 0-1 or 0-2 at follow-up [11,106]. This may partly be due to an increase likelihood of receiving rehabilitative care [105]. Additionally, despite early benefits, a prospective study demonstrated that 20-year mortality rates among premature stroke patients are significantly higher than the general populace when matched for age, sex, and calendar-year [104].…”
Section: Discussionmentioning
confidence: 98%
“…In general, younger patients exhibit better functional recovery and outcomes than older groups [105], with higher rates of younger patients achieving mRS scores of 0-1 or 0-2 at follow-up [11,106]. This may partly be due to an increase likelihood of receiving rehabilitative care [105].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with stroke aged 18-44 have significantly higher FIM scores than older patients. 6 Furthermore, return to work 12 months after stroke is associated with young age, acute stroke severity, and 3-month disability. 7 Case 2 required more than 12 months to return to work owing to the severe disability but was able to find new employment.…”
Section: Discussionmentioning
confidence: 99%
“…Younger stroke survivors are often said to have 'better' stroke recovery than their older counterparts. A recent study from Taiwan demonstrated that while younger participants indeed do tend to have better discharge functional independence measure scores, most young patients have at least some disabilities after stroke [39]. A 2020 feasibility trial of early vocational training out of the UK noted significant changes in vocational status after stroke for both intervention and control patients.…”
Section: Rehabilitation and Recovery For Stroke In The Youngmentioning
confidence: 99%